The Ignacy Łukasiewicz Memorial Museum of Oil and Gas Industry in Bóbrka and historical monuments of petroleum and salt industries in the vicinity of Krosno (the Polish Outer Carpathians) - Radwański, Andrzej B. (Geotourism/Geoturystyka)
The beginnings of petroleum industry in Poland are connected with the opening of the first “rock oil mine” in Bóbrka village near Krosno, in 1854, thanks to the initiative of three gentlemen: Tytus Trzecieski, graduated farmer and miner, and investor, Karol Klobassa-Zrencki, landowner and Ignacy Łukasiewicz, pharmacist and inventor of oil distillation. In 1961, at the site of this first “oil mine” the Ignacy Łukasiewicz Memorial Museum of Oil Industry was opened in Bóbrka. The exhibition includes: the Open-Space Museum with a number of valuable pieces and the outline of museum history and development plans, the outline of geological setting of the Bóbrka Fold, the short geotouristic trail named “The Birthplace of the World Petroleum Exploitation”, which connects the localities important for the early history of the oil industry (Bóbrka, Chorkówka, Krosno, Rogi, Wietrzno and Równe) as well as the sites known for exploitation of mineral waters (Iwonicz Zdrój and Rymanów Zdrój spas). Both the Open- Space Museum in Bóbrka and the educational trail in the vicinity of Krosno will be the part of trans-border geotourist trail Starunia-Boryslav-Lviv-Bóbrka-Wieliczka-Kraków named: “Traces of large extinct mammals, earth wax, oil and salt”.